On human rights - Griffin, James 1933- (Oxford University Press, 2008)
Traces the idea of a natural right from its origin in the late Middle Ages, when the rights were seen as deriving from natural laws, through the seventeenth and eighteenth centuries, when the original theological background was progressively dropped and 'natural law' emptied of most of its original meaning. By the end of the Enlightenment, the term "human rights" (droits de l'homme ) appeared, marking the purge of the theological background. But the Enlightenment, in putting nothing in its place, left us with an unsatisfactory, incomplete idea of a human right.Griffin shows how the language of human rights has become debased. There are scarcely any accepted criteria, either in the academic or the public sphere, for correct use of the term. He takes on the task of showing the way towards a determinate concept of human rights, based on their relation to the human status that we all share. He works from certain paradigm cases, such as freedom of expression and freedom of worship, to more disputed cases such as welfare rights--for instance the idea of a human right to health. His goal is a substantive account of human rights--an account with enough content to tell us whether proposed rights really are rights. Griffin emphasizes the practical as well as theoretical urgency of this goal: as the United Nations recognized in 1948 with its Universal Declaration, the idea of human rights has considerable power to improve the lot of humanity around the world